Bathing without water, and other stories of everyday hygiene practices and risk perception in urban low-income areas: the case of Lilongwe, Malawi. (October 2017) - Rusca, Maria; Alda-Vidal, Cecilia; Hordijk, Michaela; Kral, Nienke
Hygiene plays a key role in tipping the balance towards reduction of diarrhoeal and other infectious diseases. Yet it has often been overlooked, positioned as a "supporting rider" of water supply and sanitation services, or narrowly understood as handwashing. By focusing on handwashing infrastructure as proposed for the monitoring of Sustainable Development Goal (SDG) 6, development actors might miss the opportunity of capturing hygiene practices that are socially embedded and can act as a catalyst for change and risk reduction. We develop this argument by presenting an in-depth examination of hygiene practices in a low-income neighbourhood of Lilongwe, Malawi. Despite the high poverty levels and the constant water shortages in the area, a number of water-intensive hygiene practices are consistently carried out, proving that hygiene is central to residents' everyday lives. Development projects should start by identifying these practices and by reflecting on the extent that these already work or can be made to work for reducing health-related risks.